Endothelial progenitor cells: Are they displaying a function in autoimmune disorders?. (October 2016) - Ferrante, Angelo; Guggino, Giuliana; Di Liberto, Diana; Ciccia, Francesco; Cipriani, Paola; Balistreri, Carmela Rita; Sireci, Guido; Giacomelli, Roberto; Triolo, Giovanni
Highlights: Endothelial Progenitor Cells (EPCs) are bone marrow derived cells able to differentiate in mature endothelial cells (EC). EPCs contribute to the generation of new vessels, connecting to fibronectin, and forming colonies and/or colony forming units. EPCs can be actively considered part of endothelial damage in several autoimmune disorders. The possibility to measure the endothelium damage should be considered of interest to predict the patient out-come. The EPCs proliferative and regenerative role could be considered for therapeutic applications. Abstract: Endothelial Progenitor Cells (EPCs) are bone marrow derived cells able to differentiate in mature endothelial cells (EC) contributing to the generation of new vessels, connecting to fibronectin, and forming colonies and/or colony forming units. Since circulating EPCs can be actively considered part of endothelial damage in several cardiovascular diseases and autoimmune disorders the possibility to have a measure for endothelium damage should be considered of interest to predict the patient out-come. At the same time the EPCs proliferative and regenerative role could be considered for therapeutic applications. Studies have been performed to elucidate the role of EPCs in Systemic Sclerosis and many review and articles published on this topic. In the present paper we aimed to review the role of EPCs in other autoimmune disorders.